Análise da influência de actinídeos maiores e menores em combustíveis nucleares irradiados - Jean Anderson Dias Salomé (2016)
With the proposal of new fuels, coming from the reprocessing and recycling of burned fuels, in fourth-generation reactors or in hybrid systems, their final composition changes significantly. The objective of this work is, analyzing two systems that use reprocessed fuels, VHTR (very high temperature gas reactor) and ADS (hybrid subcritical accelerator system), to verify the behavior of these fuels after burning and compare them with the behavior of a standard PWR (pressurized water reactor). Major actinides (uranium and plutonium) and minor actinides (neptunium, americium and curium) will be followed, with a general approach to the contribution of fission products. The analyzed parameters are radioactivity and decay heat. For this study, the ORIGEN 2.1 code was used. It is expected to contribute to possible changes in swimming pool projects or temporary dry repositories and in permanent repositories, depending on the variation in the final composition of these fuels and their respective behavior after removal from the reactor or irradiation system.